An Integrated Business Planning Model as a Strategy to Improve Organizational Sustainability - Sugiharto S; M. Helmy Rahman; Naila Alifah Putri; M. Nurul Fikri Abdillah; Alma Daniyah; Muzzaki Putra Mahatir; M. Haqqi Annazily (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Business planning plays a very strategic role in determining the direction, sustainability, and success of a business organization. In practice, there are still many business actors who run their businesses without systematic planning, thus potentially facing various problems such as operational inefficiency, weak financial management, and failure to respond to changes in the business environment. This article aims to examine and develop an integrated business planning model consisting of four main pillars, namely business needs analysis, operational implementation, business performance evaluation, and capital management. This study uses a literature review method with a descriptive-analytical approach to various relevant sources of literature in the fields of management, entrepreneurship, and business planning. The results of the study show that the integration of these four pillars can form a more systematic, adaptive, and business sustainability-oriented business planning framework. This model is considered relevant for application to various business scales, especially micro, small, and medium enterprises (MSMEs) that face resource constraints but are required to remain competitive in a dynamic business environment.